Generalized Hyers-Ulam Type Stability of the 2k-Variables Quadratic β-Functional Inequalities And Function in γ-Homogeneous Normed Space - Ly Van An (International Journal of Mathematics And its Applications, 2021)
In this paper, we study to solve two quadratic β-functional inequalities with 2k-variables in γ-homogeneous complex Banach spaces and prove the Hyers-Ulam stability of quadratic β-functional equations associated two the quadratic β-functional inequalities in γ-homogeneous complex Banach spaces. We will show that the solutions of the first and second inequalities are quadratic mappings.